COMPARISON OF THE STRENGTH OF ASPHALT CONCRETE-WEARING COURSE (AC-WC) REVIEWED TOWARDS THE USE OF PC, FLY ASH AND ZEOLITE AS A FILLER IN MIXTURES - Pranoto, Putri Arifin (BANGUNAN, 2022)
Abstract: Asphalt Concrete-Wearing Course (AC-WC) is a pavement layer that is in direct contact with the vehicle's wheels. This layer is the largest in receiving traffic loads that work on the surface of the layer. Therefore, a mixture is needed to achieve high stability. For this reason, PC, fly ash, and zeolite as a filler are used in the hope of increasing the density of the mixture so as to produce high stability values.This research aims to (1) to describe the characteristics of marshall on a mixture of AC-WC with PC, fly ash and zeolite (2) to compare the strength of the AC-WC mixture in terms of the results of the Marshall parameters between PC, fly ash and zeolite. The characteristics and strengths are reviewed by marshall parameters that include stability values, flow, VIM, VMA, and VFA. The plan in this research begins with a laboratory test which include testing of aggregates, asphalt and filler. Then make the test object and continue with the Marshall test. The method of data analysis using descriptive quantitative and inferential statistics One Way Anova and the last is draw conclusions. The results showed: (1) as the asphalt content increases, the stability value tends to increase to 6% asphalt content and then decreases to 7% asphalt content where the highest average stability value is PC filler of 1299.69 kg, then zeolite filler of 1252.53 kg, followed by fly ash filler of 1005.68 kg, the flow value tends to increase with increasing asphalt content where the highest average flow value is fly ash filler of 3.89 mm, then zeolite filler of 3.59 mm, followed by PC filler of 3.06 mm, the VIM value tends to decrease with increasing asphalt content where the highest average VIM value is zeolite filler of 7.07%, then PC filler of 6.21%, followed by fly ash filler of 3.97%, VMA value tends to decrease with increasing asphalt content where the highest average VMA value is zeolite filler of 16.38%, then PC filler of 15.69%, followed by fly ash filler of 14.04%, the VFA value tends to increase with increasing the asphalt content where the highest average VFA value is fly ash filler of 72.30%, then PC filler of 61.77%, followed by zeolite filler of 57.30% (2) there is a significant difference in the average value of stability, flow, VMA between filler PC, fly ash and zeolite. The difference for the stability value is found in the fly ash filler with PC, while for flow is PC with fly ash and PC with zeolite, for VMA is fly ash with zeolite. There is no significant difference in the average VIM and VFA value between PC filler, fly ash and zeolite.Keywords: AC-WC, PC, fly ash, zeolite, marshall parameters